A unique assemblage of cosmopolitan freshwater bacteria and higher community diversity differentiate an urbanized estuary from oligotrophic Lake Michigan - Newton, Ryan J.; McLellan, Sandra L. (Frontiers in Microbiology, 2015)
Water quality is impacted significantly by urbanization. The delivery of increased nutrient loads to waterways is a primary characteristic of this land use change. Despite the recognized effects of nutrient loading on aquatic systems, the influence of urbanization on the bacterial community composition of these systems is not understood. We used massively-parallel sequencing of bacterial 16S rRNA genes to examine the bacterial assemblages in transect samples spanning the heavily urbanized estuary of Milwaukee, WI to the relatively un-impacted waters of Lake Michigan. With this approach, we found that genera and lineages common to freshwater lake epilimnia were common and abundant in both the high nutrient, urban-impacted waterways and the low nutrient Lake Michigan. Although the two environments harbored many taxa in common, we identified a significant change in the community assemblage across the urban-influence gradient, and three distinct community features drove this change. First, we found the urban-influenced waterways harbored significantly greater bacterial richness and diversity than Lake Michigan (i.e. taxa augmentation). Second, we identified a shift in the relative abundance among common freshwater lineages, where acI, acTH1, Algoriphagus and LD12, had decreased representation and Limnohabitans, Polynucleobacter, and Rhodobacter had increased representation in the urban estuary. Third, by oligotyping 18 common freshwater genera/lineages, we found that oligotypes (highly resolved sequence clusters) within many of these genera/lineages had opposite preferences for the two environments. With these data, we suggest many of the defined cosmopolitan freshwater genera/lineages contain both oligotroph and more copiotroph species or populations, promoting the idea that within-genus lifestyle specialization, in addition to shifts in the dominance among core taxa and taxa augmentation, drive bacterial community change in urbanized waters.